2010
DOI: 10.1038/sc.2010.67
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for spasticity and autonomic dysreflexia after severe spinal cord injury

Abstract: Study DesignUtilizing a complete transection spinal cord injury (SCI) model at the fourth thoracic vertebral level in adult rats, we evaluated whether blocking noxious stimuli below the injury diminishes abnormal somatic and autonomic motor reflexes, manifested in muscular spasticity and hypertensive autonomic dysreflexia, respectively. Gabapentin (GBP) is well-tolerated and currently used to manage neuropathic pain in the SCI population; evidence suggests it acts to decrease presynaptic glutamate release. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 19 publications
1
31
0
3
Order By: Relevance
“…Pharmacological approaches are currently applied to patients with SCI to treat autonomic problems in the clinical arena, while traditional palliative methods may soon be replaced with preventative methods (280,281). Although numerous attempts have been implemented to induce injured CNS axon regeneration for sensory and motor functional recovery, the aim of finding a cure for paralysis has not yet been achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological approaches are currently applied to patients with SCI to treat autonomic problems in the clinical arena, while traditional palliative methods may soon be replaced with preventative methods (280,281). Although numerous attempts have been implemented to induce injured CNS axon regeneration for sensory and motor functional recovery, the aim of finding a cure for paralysis has not yet been achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Antisympathetic drugs consist of ganglionic blockers and catecholaminergic antagonists, which often have immediate effects for responsive hypertension (122). A presynaptic calcium channel blocker, gabapentin (113,361), widely used for the treatment of neuropathic pain and epilepsy, is reported to alleviate both experimental spasticity and autonomic dysreflexia by eliminating a physiological link between these aberrant reflexes, impeding neurotransmission of noxious stimuli into the spinal cord (281,282).…”
Section: Therapeutic Strategies For Cardiovascular Dysfunction After Scimentioning
confidence: 99%
“…Although numerous individuals with SCI are using gabapentin for the management of neuropathic pain, to date there has been no clinical evaluation of its potential efficacy in managing the incidence or severity of autonomic dysreflexia. On the contrary, however, it has recently been reported that gabapentin has striking efficacy in reducing both the severity of CRD-evoked dysreflexic hypertension and tail spasticity in response to stretch or painful pinch, in the same injured animals, weeks following complete SCI [97,98].…”
Section: Synthesis Of Future Directionsmentioning
confidence: 92%
“…It is important to note that the hypotha- [112,113,115,117,123,125]. ␣ 2 ␦ subunits: [116,142,144,145,147,[150][151][152]. GBP = Gabapentin; IML = intermediolateral nucleus; PGB = pregabalin.…”
Section: Purpose and Perspectivementioning
confidence: 99%
“…␣ 2 ␦ -containing calcium channels are found at various locations within the proposed RLS circuit ( fig. 2 ), including the dorsal horn [144] , dorsal root ganglia neurons [139,142,[144][145][146][147][148][149] , intermediolateral neurons [150] , and sympathetic pre-and postganglionic neurons [151,152] . Thus, they are in a prime position to control the excitability of the circuitry at the various points that may be involved in the symptomatology of RLS.…”
Section: The ␣ 2 ␦ Calcium Channel Subunit and The Effects Of Its Ligmentioning
confidence: 99%